DEVELOPMENT OF DIAGNOSTIC TEST: MATHEMATICAL MISCONCEPTION ON THE TOPIC OF NUMBER AND ALGEBRA FOR THE SEVENTH GRADE STUDENTS IN EAST LOMBOK - Zarkasi, Zarkasi; Sugiman, Sugiman (Universitas Tanjungpura, 2019)
This study aims to: (1) look for the highest and lowest values in number and algebraic material of Junior High School in East Lombok, (2) the percentage of errors made by students when answering math problems, and (3) the diagnosis of student